PENGARUH VIDEO ANIMASI TERHADAP KEMAMPUAN BERHITUNG ANAK DI TK PERTIWI IV TALAWI - Ramli, Citra Pratiwi; Zulminiati, Zulminiati (Prodi PGPAUD, 2021)
This study aims to determine the effect of using animated videos on the numeracy skills of early childhood in Kindergarten Pertiwi IV Talawi. This study uses a quantitative approach with a quasi experimental research type. The data collection technique used a test with 10 statement instrument items. The analysis technique compares 2 average values, using the t test (t-test). But before carrying out the normality test and homogeneity test. Based on the results of the study, the average value of the experimental class using animated video was 35.93 with a standard deviation of 2.25 and the average value of the control class using non-animated counting learning videos was 29.53 with a standard deviation of 1 , 40. Based on the calculation of the t-test with the help of SPSS, the significance value (Sig.) Is obtained of 0.000 0.05, which means that there is an effect. Thus it can be concluded that the use of animated videos affects the development of children's numeracy skills in TK Pertiwi IV Talawi.